Factor rotation with non-negativity constraints - Stephen Pudney (University of Essex, Institute for Social and Economic Research (ISER), 2011)
Factor rotation is widely used to interpret the estimated factor loadings from latent variable models. Rotation methods embody a priori concepts of `complexity' of factor structures, which they seek to minimise. Surprisingly, it is rare for researchers to exploit one of the most common and powerful sources of a priori information: non-negativity of factor load- ings. This paper develops a method of incorporating sign restrictions in factor rotation, exploiting a recently-developed test for multiple inequality constraints. An application to the measurement of disability demonstrates the feasibility of the method and the power of non-negativity restrictions.
Keywords: C12; C38; I10; 330; Factor rotation; Inequality constraints; Chen-Szroeter test; Disability